EFL LEARNERS PERCEPTION IN VOCABULARY ACQUISITION USING ENGLISH NOVELS - Anggita, Windy Ayu; Rosnija, Eni; Rezeki, Yanti Sri; Bunau, Eusabinus; Rahmani, Eka Fajar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research investigates EFL learners"™ perceptions when reading English novels for their vocabulary acquisition. The participants of this research were English education study program batch 2017 at Universitas Tanjungpura. This research used a descriptive study. The data were collected through google forms for questionnaires and google meet for interviews. The questionnaire was consisting of strongly agree, agree, neutral, disagree, and strongly disagree. The result of this research the highest scored from the questionnaire was 63.3% of EFL learners who agreed they could identify the type of noun and the lowest 3.3% of EFL learners disagreed that they could identify the type of conjunction and the translations of the words. According to the results of the questionnaire and interview that have been collected, the result showed that the perception of EFL learners in reading English novels was enjoyable and helpful. It was because novel parts of literary works contain poetic words. When they read English novels, they found much new vocabulary that they rarely found in daily conversations. Furthermore, because of that, some of the EFL learners did not enjoy reading English novels. EFL learners"™ vocabulary acquisition increases, and they can learn how to use a word in a sentence. According to their perception, English novel has helped them in acquiring their vocabulary.